Review of Legacies and change in polar sciences: historical, legal and political reflections on the International Polar Year, edited by JM Shadian & M Tennberg - Dodds, Klaus (Polar Research, 2010)
The International Polar Year (IPY) of 2007–09 was an international scientific enterprise that encompassed all polar regions, and built on the legacies bequeathed by earlier endeavours stretching back to the late 19th century. The first such venture was initiated in 1882–83, the second was in 1932–33 and the last, the International Geophysical Year (IGY), occurred in 1957–58, and involved thousands of scientists working inter alia in the polar continent. Activity in the Arctic, for geopolitical reasons, was rather more limited, and was certainly not epitomized by free and unfettered scientific investigation. Sponsored by the International Council for Science, the most recent IPY was noteworthy for its explicit bi-polar focus, and its integration of the humanities and social sciences with the physical and environmental sciences. The role of indigenous communities was also notable in Arctic-based projects, a development that would have been inconceivable during the IGY. As with the IGY, however, a spectacular event in one of the theatres of scientific interest grabbed world headlines: in 1957 it was Sputnik orbiting the Earth, and in 2007 it was a Russian submersible planting a flag on the bottom of the central Arctic Ocean basin.
Keywords: Antarktis; Det internasjonale geofysiske år (IGY); bokanmeldelser; forskning; geopolitikk; internasjonal; polarområdene; samarbeid; vitenskap

Antarctica – What role for the EU? - Dodds, Klaus; Raspotnik, Andreas (European Parliament, 2023)
Keywords: Antarktis; geopolitikk; politikk